2016
DOI: 10.30684/etj.34.3b.17
|View full text |Cite
|
Sign up to set email alerts
|

A Practical and Theoretical Study of the Locally Manufactured Vacuum Solar Dryer for Fish Drying

Abstract: A theoretical and practical study was conducted for the vacuum solar dryer, which locally manufactured to drying of salted and unsalted carp Fish and compared with natural sun drying and vacuum electric dryer in Basrah province for the period from October 2011 to July 2012. The study included simplifying the Crank's equation to predict the theory moisture content compared with practical data. Solar radiation intensity, temperature in the atmosphere and in the solar dried were measured. The results indicated a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…In Basrah province, theoretical and practical research was undertaken by Al-Hilphy et al [18] for the vacuum solar dryer, who was locally made to dry salted and unsalted carp fish, and it was compared to natural sun drying and vacuum electric dryer. It was found that the moisture content of dried fish dried using a vacuum solar dryer and a vacuum electric dryer were similar, although it was much better than sun-drying.…”
Section: Introductionmentioning
confidence: 99%
“…In Basrah province, theoretical and practical research was undertaken by Al-Hilphy et al [18] for the vacuum solar dryer, who was locally made to dry salted and unsalted carp fish, and it was compared to natural sun drying and vacuum electric dryer. It was found that the moisture content of dried fish dried using a vacuum solar dryer and a vacuum electric dryer were similar, although it was much better than sun-drying.…”
Section: Introductionmentioning
confidence: 99%